CD4(+)CD25(+) regulatory T lymphocytes in bone marrow transplantation - Joffre, Olivier (Academic Press, 2006)
Induction of immunological tolerance to alloantigens would be the treatment of choice to prevent graft-versus-host disease and allograft rejection in transplantation medicine. Organisms use a variety of mechanisms to avoid potentially deadly immunity to self-antigens. The most potent self-tolerance mechanism is probably dominant tolerance assured by regulatory and suppressor T lymphocytes. It appears therefore attractive to use the same mechanism to induce transplantation-tolerance. We here review and discuss recent advances in the use of one of the best-characterized regulatory T lymphocyte populations, CD4(+)CD25(+) T cells, to prevent graft-versus-host disease and bone marrow allograft rejection.